If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(11 + -6x) + -10(9 + 12x) = 285 (11 * 15 + -6x * 15) + -10(9 + 12x) = 285 (165 + -90x) + -10(9 + 12x) = 285 165 + -90x + (9 * -10 + 12x * -10) = 285 165 + -90x + (-90 + -120x) = 285 Reorder the terms: 165 + -90 + -90x + -120x = 285 Combine like terms: 165 + -90 = 75 75 + -90x + -120x = 285 Combine like terms: -90x + -120x = -210x 75 + -210x = 285 Solving 75 + -210x = 285 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + -210x = 285 + -75 Combine like terms: 75 + -75 = 0 0 + -210x = 285 + -75 -210x = 285 + -75 Combine like terms: 285 + -75 = 210 -210x = 210 Divide each side by '-210'. x = -1 Simplifying x = -1
| (x+12)(x-15)=0 | | (5x+3)/4=-12 | | 7-9(5t-4)=47 | | 7/4x+4/3=-8 | | x=0.1666666667 | | 15c+12=2 | | 110-x=11 | | 2(1+3x)=26 | | 3t-(t+5)=6+(t+1) | | 3(4p+5)-11p= | | 8-7n-21=85 | | 711.67*2.5%= | | 2/3=4x/6 | | 15y/5=x | | x^4+6x^3+14x^2+15x-6=0 | | (4x+3)/12x=36 | | -226.8=21.6 | | (-50)-(9)= | | -2226.8=21.6y | | (7)-(-3)= | | 45x^2-60x+20=0 | | 49/n=7 | | ax+2a=4x+7a | | 4/(x-1)=(x+1)/12 | | -5+7t+16+t=11t-3-t | | y/9=5+0 | | 15x^2-x-10=18 | | 3y+2x=-4 | | 4y-13-5y=-12y+9+8y | | 3x+3(5d-18)=108 | | M=3n+8 | | -113=-(8+8x)-7x |